2014
DOI: 10.1155/2014/243247
|View full text |Cite
|
Sign up to set email alerts
|

Research on Hybrid Isolation System for Micro-Nano-Fabrication Platform

Abstract: In order to obtain better vibration suppression effect, this paper designs a semiactive/fully active hybrid isolator by using magnetorheological elastomer (MRE) and piezoelectric material. Combined with multimode control scheme, full frequency vibration suppression is achieved. Firstly, series type structure is determined for the hybrid isolator, and the structure of hybrid isolator is designed. Next, the dynamic model of hybrid isolator is derived, the dynamic characteristics measurement for MRE isolator and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Fu et al have also developed a semi-active/fully-active hybrid isolator using magnetorheological elastomer and piezoelectric material. They found that the natural frequency can be shifted by approximately 20 Hz by applying an exciting current of 1 A to the electromagnet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al have also developed a semi-active/fully-active hybrid isolator using magnetorheological elastomer and piezoelectric material. They found that the natural frequency can be shifted by approximately 20 Hz by applying an exciting current of 1 A to the electromagnet [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“… F PSA ( t ) and F MRE ( t ) are the active actuation force of PSA and the semi-active actuation force of MRE isolator generated by the electromagnetic field, respectively, which will also be computed by the designed FSC in the following section. The equivalent stiffness and damping coefficient of PSA and MRE isolator are obtained from experimental test results in Fu et al (2014) and Fu et al (2016), which are listed in Table 2.…”
Section: Modeling Of Hybrid Isolation Systemmentioning
confidence: 99%
“…For the PAS used in this article which is linear under the operating frequency range of 50 Hz by experimental test (Fu et al, 2014), the switch frequency of active and semi-active control is set as 50 Hz. On the other hand, in order to obtain the switch frequency of semi-active control and passive control, the simulations are carried out.…”
Section: Fsc Designmentioning
confidence: 99%
“…Fu et al. 18 developed a semi-active/fully active hybrid isolator by using magnetorheological elastomer and piezoelectric material, which can suppresses full frequency vibration. Han et al.…”
Section: Introductionmentioning
confidence: 99%
“…Hong and Choi 17 developed a mixed-mode-type magnetorheological fluid mount and passive rubber mounts, which can effectively reduce the unwanted vibration levels such as acceleration of structural system and force transmission. Fu et al 18 developed a semi-active/fully active hybrid isolator by using magnetorheological elastomer and piezoelectric material, which can suppresses full frequency vibration. Han et al 19 developed a hybrid mount featuring a passive rubber, magnetorheological fluid and a piezostack.…”
Section: Introductionmentioning
confidence: 99%